2014
DOI: 10.1007/s13197-014-1648-4
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric approach to texture profile analysis of kombucha fermented milk products

Abstract: In the present work, relationships between the textural characteristics of fermented milk products obtained by kombucha inoculums with various teas were investigated by using chemometric analysis. The presented data which describe numerically the textural characteristics (firmness, consistency, cohesiveness and index of viscosity) were analysed. The quadratic correlation was determined between the textural characteristics of fermented milk products obtained at fermentation temperatures of 40 and 43°C, using mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…They also showed that the concentration of applied kombucha starter has no significant influence on textural characteristics of produced samples. Malbaša et al 2014 investigated textural characteristics of kombucha fermented dairy products obtained by kombucha inoculums cultivated from various teas at the temperature of 40 and 43°C (Malbaša et al 2014). Their obtained results are in accordance with the results in this research and indicate insignificant influence of inoculum tea type on textural characteristics.…”
Section: Textural Characteristicssupporting
confidence: 77%
“…They also showed that the concentration of applied kombucha starter has no significant influence on textural characteristics of produced samples. Malbaša et al 2014 investigated textural characteristics of kombucha fermented dairy products obtained by kombucha inoculums cultivated from various teas at the temperature of 40 and 43°C (Malbaša et al 2014). Their obtained results are in accordance with the results in this research and indicate insignificant influence of inoculum tea type on textural characteristics.…”
Section: Textural Characteristicssupporting
confidence: 77%
“…Kombucha is a refreshing drink obtained by fermentation, for about 14 d with a symbiotic culture of several indigenous bacteria (Acetobacter and Gluconobacter) and yeasts (Saccharomyces spp and non-Saccharomyces spp) (Malbasa et al, 2014). Most of the studies suggest that ''tea fungus'' came from the Southeast of Asia, Japan, Tibet or Manchuria and dates back thousands of years (Jarrell, Cal, & Bennett, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The texture of fermented milk product is important with regard to the quality of the products. The literature data indicate significant influence of milk composition, inoculum tea type and concentration and of transglutaminase addition on the textural characteristics of fermented milk products obtained by kombucha (Malbaša et al, 2015;Iličić et al, 2013;.…”
Section: Textural Characteristicsmentioning
confidence: 99%